Konsep Syura dalam Alquran - Bakry, Kasman (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2018)
The concept of SyÅ«rÄ is one of the concepts existed in the Qur'an, and it is monumentalized by Allah Almighty in the Qur'an as one name of its chapters, al-SyÅ«rÄ. The word â€œSyÅ«rÄâ€ in etymologically has two defnitions, that are: â€œto reveal and expose something or take somethingâ€. While in the perspective of terminology, there are several defnitions, one of which is â€œa process of exposing various opinions with argumentation in an issue, tested by experts who has capabilities on the issue in order to conclude the right and the best implemental solution so that the expected objectives can be achievedâ€. This study focuses on the discussion about the status of SyÅ«rÄ and its urgency in Islam, the concept of SyÅ«rÄ in the Qur'an, as well as the diï¬€erences between the SyÅ«rÄ and Democracy. This research used qualitative methods with the theological normative approach, resulting in a conclusion that SyÅ«rÄ is very important as one of the basic steps and most important rule of law enforcement in Islam on various aspects of the life of mankind.